Focusing Adverbs in Classical Greek: μάλιστα (Minerva, 2017)
This article presents a research on the functional domain of classical Greek μάλιστα. The whole text of Thucydides has been selected as relevant corpus and only the uses as quantifier have been taken into account, while the analysis is based on semantic and syntactic properties. Besides its function as a predicate adjunct expressing Degree, three other functions have been identified: as a focus-sensitive sentence adjunct; as a particularizer or restrictive-focusing adverb; and as a conjunctive adverb elaborating on the relation expressed by additive connectors.
Keywords: ancient greek; μάλιστα; focusing adverbs; conjunctive adverbs; particularizers